Risk factors and outcomes in children with high-risk B-cell precursor and T-cell relapsed acute lymphoblastic leukaemia: combined analysis of ALLR3 and ALL-REZ BFM 2002 clinical trials - Eckert, Cornelia; Parker, Catriona; Moorman, Anthony V; Irving, Julie Ae; Kirschner-Schwabe, Renate; Groeneveld-Krentz, Stefanie; Révész, Tamas; Hoogerbrugge, Peter; Hancock, Jeremy; Sutton, Rosemary; Henze, Guenter; Chen-Santel, Christiane; et al. (European journal of cancer, 2021)
AIM: Outcomes of children with high-risk (HR) relapsed acute lymphoblastic leukaemia (ALL) (N = 393), recruited to ALLR3 and ALL-REZ BFM 2002 trials, were analysed. Minimal residual disease (MRD) was assessed after induction and at predetermined time points until haematopoietic stem cell transplantation (SCT). METHODS: Genetic analyses included karyotype, copy-number alterations and mutation analyses. Ten-year survivals were analysed using Kaplan-Meier and Cox models for multivariable analyses. RESULTS: Outcomes of patients were comparable in ALLR3 and ALL-REZ BFM 2002. The event-free survival of B-cell precursor (BCP) and T-cell ALL (T-ALL) was 22.6% and 26.2% (P = 0.94), respectively, and the overall survival (OS) was 32.6% and 28.2% (P = 0.11), respectively. Induction failures (38%) were associated with deletions of NR3C1 (P = 0.002) and BTG1 (P = 0.03) in BCP-ALL. The disease-free survival (DFS) and OS in patients with good vs poor MRD responses were 57.4% vs 22.6% (P < 0.0001) and 57.8% vs 32.0% (P = 0.0004), respectively. For BCP- and T-ALL, the post-SCT DFS and OS were 42.1% and 56.8% (P = 0.26) and 51.6% and 55.4% (P = 0.67), respectively. The cumulative incidences of post-SCT relapse for BCP- and T-ALL were 36.9% and 17.8% (P = 0.012) and of death were 10.7% and 25.5% (P = 0.013), respectively. Determinants of outcomes after SCT were acute graft versus host disease, pre-SCT MRD (≥10-3), HR cytogenetics and TP53 alterations in BCP-ALL. CONCLUSION: Improvements in outcomes for HR ALL relapses require novel compounds in induction therapy to improve remission rates and immune targeted therapy after induction to maintain remission after SCT. TRIAL REGISTRATION: ALLR3: NCT00967057; ALL REZ-BFM 2002: NCT00114348.
Keywords: Graft vs Host Disease; mladiství; progrese nemoci; Biomarkers, Tumor; dítě; Clinical Trials as Topic; nemoc štěpu proti hostiteli; Gene Dosage; pre-B-buněčná leukemie; Karyotype; Mutation; Risk Assessment; Progression-Free Survival; lymfoblastická leukemie-lymfom z prekurzorových T-buněk; rizikové faktory; Humans; přežití bez známek nemoci; Female; transplantace hematopoetických kmenových buněk; protokoly protinádorové kombinované chemoterapie; Child, Preschool; Male; Antineoplastic Combined Chemotherapy Protocols; Hematopoietic Stem Cell Transplantation; Disease-Free Survival; Recurrence; reziduální nádor; ženské pohlaví; Time Factors; klinické zkoušky jako téma; časové faktory; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Child; Risk Factors; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Neoplasm, Residual; hodnocení rizik; genová dávka; doba přežití bez progrese choroby; mutace; předškolní dítě; recidiva; Adolescent; Disease Progression; nádorové biomarkery; lidé; karyotyp; mužské pohlaví